دور الإتصالات التسويقية المتكاملة في جذب العملاء دراسة حالة شركة التأمين وإعادة التأمينCIAR – وكالة سوق أهراس - نور الهدى بن دادة (My University, 2022)
This research dealt with the topic of "The Role of Integrated Marketing Communications in Attracting Customers", which is a model adopted by the largest international orgatnisations, which highlights Algeria's attempts to advance the service sector, especially insurances. This research aims to to determine the role of integrated marketing communications in attracting customers in the insurance and reinsurance company Ciar. the research sought to achieve a number of cognitive and applied objectives. In the theoretical aspect, we approached the definition of integrated marketing communications and its forms and the impact of these forms on customers, and in order to achieve the objectives of the study, the hypotheses were tested through the practical side, in which data and informations were collected by a questionnaire distributed to a sample of 50 individuals from the clients of the insurance and reinsurance company Ciar, then the process of the collected data was done by a set of statistical methods that fit the research, which produced several results indicating the existence of customers awareness of the efforts of the insurance and reinsurance company Ciar and a statiscally significant effect and correlation of integrated marketing communications on attractiong customers in general, and it was found that sales stimulation is the most effective form of communication. The research concluded that it is necessary to apply integrated marketing communications as a system and to use its outputs in building a successful marketing strategy. ........................................... تناول هذا البحث موضوع " دور الإتصالات التسويقية المتكاملة في جذب العملاء" وهو نموذج تم تبنيه من طرف أكبر المؤسسات العالمية، الأمر الذي يسلط الضوء على محاولات الجزائر للنهوض بالقطاع الخدمي وبالأخص التأمينات وهدفه ذا البحث إلى تحديد دور الإتصالات التسويقية المتكاملة في جذب العملاء في شركة التأمين وإعادة التأمين Ciar ، وسعى البحث إلى تحقيق جملة من الأهداف المعرفية والتطبيقية، تطرقنا في الجانب النظري إلى مفهوم الإتصالات التسويقية المتكاملة وأشكالها وتأثير هذه الأشكال على العملاء، ومن أجل تحقيق أهداف البحث تم إختبار الفرضيات من خلال الجانب التطبيقي والذي تم فيه جمع البيانات والمعلومات بواسطة إستبيان موزع على عينة مكونة من 50 فردا من عملاء شركة التأمين وإعادة التأمين Ciar ، ولأجل معالجة البيانات تم إستخدام مجموعة من الأساليب الإحصائية التي تناسب البحث والتي أفرزت عدة نتائج تشير إلى وجود إدراك العملاء لجهود شركة التأمين وإعادة التأمين Ciar ووجود تأثير وإرتباط ذو دلالة إحصائية للإتصالات التسويقية المتكاملة على جذب العملاء بشكل عام، كما تم التوصل إلى أن تنشيط المبيعات هو أكثل أشكال الإتصال فعالية . وخلص البحث إلى ضرورة تطبيق الإتصالات التسويقية المتكاملة كنظام وإستخدام مخرجاته في بناء إستراتيجية تسويقية ناجحة.